Cell surface interactions of coxsackievirus A9 and human parechovirus 1 - Merilahti, Pirjo (Annales Universitatis Turkuensis D 1283, 2017)
Coxsackievirus A9 (CV-A9) and human parechovirus 1 (HPeV-1) belong to family Picornaviridae, genera Enterovirus and Parechovirus respectively. CV-A9 has been associated with aseptic meningitis, myocarditis in addition to other mild and/or severe clinical manifestations. HPeV-1 infection most commonly induces mild gastrointestinal and respiratory symptoms, but also more severe manifestations such as myocarditis and transient paralysis may occur. HPeV-1 infection is very common in children and neonates; likewise, CV-A9 infection occurs most often in children. Vaccines, antivirals or drugs against these viruses do not exist. CV-A9 and HPeV-1 harbor an arginine-glycine-aspartic acid (RGD) –motif on their capsids, which is the binding motif of some integrins, a group of heterodimeric cell adhesion receptors. Integrins participate in many cellular functions, for example in cell signaling and organization of the intracellular cytoskeleton. The RGD-binding integrins are hypothesized to act as cell surface receptors for CV-A9 and HPeV-1. In this study, the receptor tropism of CV-A9 and HPeV-1 was extensively analyzed in vitro. Different mammalian cell lines for the receptor studies were used, and applied methods such as blocking experiments with neutralizing antibodies and receptor antagonists were utilized. The results were mainly analyzed with fluorescence microscopy. The in vitro studies suggest that CV-A9 can penetrate into the cells without integrins. Instead, CV-A9 binds to heat shock protein family A member 5 (HSPA5) on the cell surface with heparan sulfate (HS) and β2-microglobulin (β2M) acting as accessory receptors. However, the results suggest that HPeV-1 utilizes αVβ1 integrin as its primary receptor, but HS and β2M act as accessory receptors for HPeV-1 similarly to CV-A9.